2008
DOI: 10.1007/s11605-008-0704-7
|View full text |Cite
|
Sign up to set email alerts
|

Routine Liver Biopsy to Screen for Nonalcoholic Fatty Liver Disease (NAFLD) during Cholecystectomy for Gallstone Disease: Is it Justified?

Abstract: Fifty-five percent of patients with GD have associated NAFLD. Awareness of this association may result in an earlier diagnosis. The high prevalence of NAFLD in patients with GD may justify routine liver biopsy during cholecystectomy to establish the diagnosis, stage, and possible direct therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
1
21
0
8
Order By: Relevance
“…That the prevalence of NAFLD can further increase as the number of obese people in Asia increases is supported by the findings that 65 and 85% of subjects with a BMI of 30–40 and ≥40 kg/m 2 , respectively, had NAFLD [29]. Despite its high prevalence and potential impact, recent studies highlighted that, even among high-risk patients, 87% of people did not know they had NAFLD [30] and 51% of healthy potential liver donors were incidentally confirmed as having NAFLD by liver biopsy [31], indicating that alarming proportions of patients with NAFLD are unaware of their illness and are undiagnosed. Therefore, a simple risk score that can efficiently and effectively screen high-risk individuals for NAFLD in communities, as well as in clinical settings, could help improve personal and population health, and public awareness and education about this less known disease.…”
Section: Discussionmentioning
confidence: 95%
“…That the prevalence of NAFLD can further increase as the number of obese people in Asia increases is supported by the findings that 65 and 85% of subjects with a BMI of 30–40 and ≥40 kg/m 2 , respectively, had NAFLD [29]. Despite its high prevalence and potential impact, recent studies highlighted that, even among high-risk patients, 87% of people did not know they had NAFLD [30] and 51% of healthy potential liver donors were incidentally confirmed as having NAFLD by liver biopsy [31], indicating that alarming proportions of patients with NAFLD are unaware of their illness and are undiagnosed. Therefore, a simple risk score that can efficiently and effectively screen high-risk individuals for NAFLD in communities, as well as in clinical settings, could help improve personal and population health, and public awareness and education about this less known disease.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that GD was a highly prevalent condition in NAFLD patients,15,16,17,18 and that it may represent an independent risk factor for NAFLD 19. In a large series of 524 Italian patients with biopsy-proven NAFLD, Fracanzani and colleagues demonstrated that the prevalence of GD progressively increased with advancing fibrosis and with the severity of necroinflammatory activity 20.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally there have been various publications investigating an association between NAFLD and GD showing increased GD prevalence in NAFLD patients. [9][10][11][12][13][14] However there is no data available showing a causal relationship on this issue regarding gallbladder motility in patients with NAFLD. The present study was designed to investigate the relationship between fasting gallbladder volumes, ejection fraction, residual volume, gallbladder thickness, biochemical values, histopathological parameters, and anthropometric measurements in patients with biopsy-proven NAFLD without GD and healthy controls.…”
Section: Introductionmentioning
confidence: 99%